Stress-related breathing problems: an issue for elite swimmers - Kristiansen, E.; Abrahamsen, F. E.; Stensrud, T. (Journal of Swimming Research, 2012)
The purpose of this preliminary study was to test if there are any links between breathing problems, and physiological and psychological recovery (or perceived lack thereof) in elite swimmers. In order to do so, twenty-four elite competitive swimmers (range 15-25 years, Mage = 18.25 years, SD = 1.60), from two swimming clubs in Norway both performed three physiological tests for bronchial hyperresponsiveness (BHR) and also completed a series of psychological questionnaires. The results are important for coaches, as it was revealed an alarmingly high prevalence of BHR. Possible links between physiological and psychological stress markers in athletes are explained by the use of Cognitive Activation Theory of Stress (CATS). Correlations revealed an association between one perfectionism factor (concern over mistakes) and the recovery scale (balance between training and recovery), practically meaning there might be a relationship between breathing problems and reduced recovery. However, a mastery climate may protect the swimmers against both perfectionism and burnout, helping their recovery in the long run. In conclusion, there is evidence that we need more research about this possible (breathing) stress-recovery imbalance in order to identify under recovery and avoid more severe negative consequences for elite swimmers.